It was a dark and stormy night—Investigation of acrylate storage tank explosions. Issue 2 (28th September 2021) - Kas, Kathleen; Morrison, Delmar "Trey"
Abstract: In the early morning hours of May 16, 2012, a thunderstorm rolled into the Bristol, PA, plant that produced acrylic polymers. Lightning struck in the tank farm area. Within seconds, an ethyl acrylate tank exploded and was followed a few minutes later by a butyl acrylate tank explosion. The explosions and ensuing fire led to a lengthy shutdown; fortunately, there were no injuries. This article details the investigation into the complex sequence of events that led to the two explosions. The tank installations complied with the industry lightning standards, but if the tanks met industry standards, why did the explosion happen? While the exact mechanism could not be determined with certainty, the ignition of the atmosphere in the ethyl acrylate tank most likely occurred from a spark discharge inside the tank's headspace, likely between internal components at different electrical voltage potentials. This type of mechanism could invalidate the Faraday Cage assumption inherent in current industry guidance and may represent a hazard that is not currently well‐recognized. It should also be noted that, while lightning cannot be prevented, the outcome of a lightning strike can be mitigated by the use of safeguards such as inertion, flame arresters, diking, and foam systems.